The Classroom Management Strategies in Improving Students' Learning Discipline in the Fourth Grade at SD Negeri 13 Lolong - Yulianda, Retno; Efrina, Gusnita; Oktira, Yona Syaida; Efendi, Nofriza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Low student learning discipline, such as tardiness, not doing assignments, and disorderly behavior in class, becomes an obstacle in the learning process. This study aims to describe classroom management strategies in improving student learning discipline in class IV SD Negeri 13 Lolong. This research uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation of the class teacher, Islamic Religious Education teacher, English teacher, and five students. The results showed that teachers implemented strategies such as making rules with students, giving awards, seating arrangements, daily picket schedules, and exemplary. Improved discipline indicators include responsibility and cooperation. Supporting factors for this strategy include a well-organized physical classroom environment, positive emotional relationships, and a good classroom organizational structure. The inhibiting factors include the lack of discipline awareness from within students, the habit of arriving late, and the teacher's delay in starting the lesson. Thus, classroom management strategies that are implemented consistently and appropriately are proven to be able to significantly improve student learning discipline.